Fabrique du scandale et rivalités mémorielles en France et en Europe (1550-1697) - Zanin, Enrica; Perona, Blandine; Moreau, Isabelle (S@voirs humanistes, 2022)
In 1550, the theological notion of "scandal" was put forward in Calvin's treatise Concerning Scandals. The reformer invited his coreligionists not to be afraid of scandal and not to concern themselves with fama. Focusing on the notion of scandal, the present study demonstrates the role of reputation in interdenominational conflicts. The Protestant-Catholic conflicts become a battle of conflicting memories. As Catholics and Protestants fight to impose their own narratives, it impacts the writing of history. Scandal, thus, is crucial on both sides; it constitutes a polemical tool in a war fought with the pen and the press where libels are tearing apart the nascent 'public space'. Following its theological making, the legal making of scandal then gradually allows the monarchy to regain control of its torn 'public space'. This book thus analyses the emerging of scandal in its modern understanding: an event constructed as a narrative through media coverage for political purposes, which brings into crisis the common basic standards and values of a society due to the transgressive nature ofthe acts or words it accounts for.